The Conception of Free Labour in the Socratics and Aristotle - Plácido, Domingo (Gerión. Revista de Historia Antigua, 2012)
Xenophon and the other Socratics set out in 4th Century the recovery of client relationships based on the charis as an alternative to the critical situation of chattel slavery. In this way the problems of the Empire and those derived from democratic citizenship connected to the misthos are avoided. In the same line, with more systematic theoretical proposals, Aristotle develops the politeia as an organization that demarcates citizenship in accordance with the real situation of each person with respect to work and leisure compared to the democratic city’s statutory system. Manual labour becomes a criterion with which to define the rights of citizenship. Aristotle perceives how the economic changes in his age favour the breaking up of the basis of the classical city. The same problems underlie the literary and intellectual expressions of the transition to Hellenism.
Keywords: slavery; clientelship; citizenship; Socratic school; Aristotle; Hellenism.